Effects of hydroxymethylfurfural from chemical-protein interaction networks in Apis mellifera, Bos taurus and Homo sapiens species - Ribeiro, Bruna Santos; Alves, Janainne Nunes; Paixão, Débora Martins; Santos, Hércules Otacílio; Santos , Wagner Silva dos; Ferreira, Renata Gabriela Chaves; Oliveira, Sheila Rodrigues; Almeida, Anna Christina de; Santos, Eliane Macedo Sobrinho (Revista de Ciências Agroveterinárias, 2025)
Hydroxymethylfurfural (HMF) is a compound used as an indicator of food and feed quality. Its concentration can vary according to storage and processing conditions, being influenced by factors such as temperature, pH, and storage time. HMF has antioxidant, anti-inflammatory, and anti-hypoxic properties, and can protect cells against oxidative damage. However, at high concentrations, HMF can be cytotoxic, mutagenic and carcinogenic, which denotes the need to understand its mechanisms of action in different organisms. In this study, chemical-protein interaction networks were constructed, within the scope of bioinformatics, to analyze the effects of HMF on Apis mellifera, Bos taurus and Homo sapiens. In bees, HMF interacts with proteins such as GB17880-PA and LOC551167 that are associated with multi-drug resistance and molecule transport, suggesting a role in defending against oxidative stress. In cattle, HMF interacts with proteins such as CYGB and SDHA, involved in respiratory functions and energy production, also indicating potential protective effects against oxidative damage. In humans, HMF acts on proteins such as HBB and SULT1A2, related to hormone metabolism and immunity, with effects that vary according to the dosage and metabolic pathway activated. According to the results found, it is observed that HMF can modulate important biological processes, such as oxidative phosphorylation, purine metabolism and cell signaling. However, in vitro and in vivo functional studies are necessary to confirm these interactions and elucidate the molecular mechanisms involved.